O Neolítico Antigo da Baixa Estremadura : as investigações dos últimos cinco anos - Cardoso, João Luís (2016)
The lirst results obtained in the last five years in research about the Early Neolithic in Lower Estremadura (including the peninsulas of Lisboa and Setúbal) are presented. There was an advance in the understanding resulting from preventive excavations. The settlements are distributed, as far as their characterization permits, between specialized sites and pluriannual residential sites, while the necropolis corresponds to the use of natural caves. The dates now obtained and published for the first time indicate the Neolithic presence more ancient known for residential sites, dating from the Early Neolithic, ca. 5400-4900 BC, in which the ceramics impressed by "Cardium" are residual, while the sole necropolis dated reports to a time corresponding to the second hallf of the VI millennium BC though the registry is absent of the above mentioned ceramic productions, in contrast with the abundance of the decorated ceramics by incisive motifs, impressed and plastic. The transition to the Middle Neolithic is located though with the limitations resulting from the type of analysis and the materials used in the second hall of the V millennium BC, apparently with the persistence of the decorated ceramics from early tradition.